A corneal elastic dynamic model derived from Scheimpflug imaging technology - Shih, Po-Jen; Cao, Huei-Jyun; Huang, Chun-Ju; Wang, I-Jong; Shih, Wen-Pin; Yen, Jia-Yush (Ophthalmic & physiological optics, 2015)
Purpose To simultaneously extract the corneal Young's modulus and the damping ratio from Scheimpflug imaging data. Methods A spherical diaphragm model can better represent the geometry and physics of an eyeball than the popular mass‐spring‐damper model. This research derived the dynamic model of a water‐filled spherical diaphragm based on the hydrodynamics and wave propagation theories. By applying modal analysis on the model, one can decouple the cornea vibration into individual modes and reconstruct the air puff vibration from the decoupled responses. By matching this response with the Scheimpflug imaging data from the Corvis® ST, it was then possible to extract multiple physiological properties as desired. Results The dynamic modal analysis was employed to extract the corneal physiological properties of 25 Taiwanese normal subjects. Specifically, the corneal Young's moduli and damping ratios were estimated. In fact the model is dependent on the physiological parameters such as cornea thickness, densities, and intraocular pressure. It is thus also possible to extract these parameters through multi‐goal minimisation processes. Conclusions The spherical diaphragm model was able to better describe the dynamic response of the eyeball. The model analysis also provides additional corneal physiological properties that were not available through other means.